2020
DOI: 10.1093/cid/ciaa1803
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Severe Acute Respiratory Syndrome Coronavirus 2 Neutralizing Activity in Prepandemic Sera From Individuals With Recent Seasonal Coronavirus Infection

Abstract: Cross-reactive immune responses elicited by seasonal coronaviruses might affect severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) susceptibility and disease outcomes. We measured neutralizing activity against SARS-CoV-2 in prepandemic sera from patients with prior polymerase chain reaction scan-confirmed seasonal coronavirus infection. Although neutralizing activity against seasonal coronaviruses was detected in nearly all sera, cross-reactive neutralizing activity against SARS-CoV-2 was undetectabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
66
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 13 publications
11
66
0
Order By: Relevance
“…Here, we observed increases in seasonal HCoV spike reactive IgG antibodies in SARS-CoV-2 positive cohort. SARS-CoV-2 has been shown to stimulate OC43 memory B cells through conserved epitopes in the SARS-CoV-2 S glycoprotein S2 subunit and serum samples from subjects with recent HCoV infection contain SARS-CoV-2 cross-reactive but not cross-neutralizing antibodies (54). As de novo IgG cross-reactivity with HCoV-HKU1 and HCoV-OC43 spike protein was not observed in SARS-CoV-2 challenged NHPs (Figure 5A), the presence of prior humoral memory to seasonal HCoV appears necessary to drive cross-reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we observed increases in seasonal HCoV spike reactive IgG antibodies in SARS-CoV-2 positive cohort. SARS-CoV-2 has been shown to stimulate OC43 memory B cells through conserved epitopes in the SARS-CoV-2 S glycoprotein S2 subunit and serum samples from subjects with recent HCoV infection contain SARS-CoV-2 cross-reactive but not cross-neutralizing antibodies (54). As de novo IgG cross-reactivity with HCoV-HKU1 and HCoV-OC43 spike protein was not observed in SARS-CoV-2 challenged NHPs (Figure 5A), the presence of prior humoral memory to seasonal HCoV appears necessary to drive cross-reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-reactivity with seasonal coronaviruses has to be considered. Even if recently, pre-existing HCoV-NL63 antibody response crossreacting with some SARS-CoV-2 antigens was detected in both pre-and mid-pandemic infected individuals [28], though no cross-reactivity of serology methods with the seasonal coronavirus was reported [29] and no neutralizing activity of SARS-CoV-2 in pre-pandemic sera was observed [30]. All IgT-positive serum samples were positive for antibodies against the RBD of S protein (Biosynex COVID19 BSS).…”
Section: Discussionmentioning
confidence: 97%
“…While some studies have found that these cross-reactive antibodies can neutralize SARS-CoV-2 in vitro, others have not (61,91,92). In patients, cross-reactive antibodies are also not associated with protection against SARS-CoV-2 infection or severe COVID-19 (61).…”
Section: Discussionmentioning
confidence: 99%